Entre o "cá" e o "lá": educação e trabalho na vida dos jovens migrantes do Alto Jequitinhonha, MG - Conceicao Aparecida Luciano (2013)
The following research has as an objective to analyse the relationship between work and training in the lives of rural youth, seasonal migrants Alto Jequitinhonha that will employ cutting sugar cane in São Paulo and other regions of Brazil, in large mills producing sugar and alcohol. Migrants permanently temporary pass 8-9 months in a cut cane plants, repeating the same trajectory of parents, labor relations increasingly precarious and inhuman. These are part of the large contingent of reserve labor workforce, weakened politically and socially, always vying for jobs more precarious service sector with migrants from other regions. Thus, the question that this paper set out to answer is how these young Jequitinhonha perceive themselves in their careers. As these young people understand the formal (school) and informal (family) who received and their impact on life. The knowledge received from parent to read in the earth expands in other professions or is a knowledge that can only be used in the region of origin? What are the aspirations of young people regarding the professional future? In their future projects included is a new professional qualification? To answer these questions the research was based on observation predominantly qualitative data. A semi-structured interview was the primary data collection technique to be a legitimate space in the production of knowledge, allowing a dialogical relationship between respondent and researcher. Content analysis was used for the interviews. Through field research and data collection can understand that young rural migrants do not include the school in their professional projects for future work is the only possibility of social mobility and not the school, these young people have to live in the greatest dream Jequitinhonha and get a job outside the area, near the plantation, since rural activity is not seen as chance of survival. The theoretical framework was the work of Candido (1975); Durhan (1978), Martins (1975, 1986, 1991, 2002, 2012) Woortmann (1984, 1990) Carneiro (1998, 2007, 2009) among others, as key interlocutors because they are the great thinkers of rural issues in Brazil.